SCIENTIFIC-PRACTICAL CONFERENCE «ACTUAL PROBLEMS OF PEDIATRICS» KALUGA, NOVEMBER, 10-11, 2009 - A.A. Author ("Paediatrician" Publishers LLC, 2009)
(Voprosy sovremennoi pediatrii - Current Pediatrics. 2009;8(6):158)